Analisis Rasio Profitabilitas Untuk Menilai Kinerja Keuangan PT. Airasia Indonesia TBK, Periode 2020-2022 - Miftakhul Qurotul Aini; Fina Silfya; Adelina Citradewi (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Using Profitability Ratio Analysis to Evaluate Financial Performance (Study at Pt AirAsia Indonesia, 2020-2022). The objective of this study is to provide a profitability ratio analysis of PT AirAsia Indonesia's financial performance from 2020 to 2022. Descriptive qualitative research was used for the study. Secondary data from PT Air AsiaIndonesia's financial reports for the years 2020 to 2022 serve as the data source. Based on profitability ratios like Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), and Gross Profit Margin (GPM), the company's financial performance has not yet reached industry standards, according to the study's findings. Even though PT AirAsia Indonesia Tbk's sales are quite substantial and even experienced a significant increase, the company is not necessarily considered to have performed well. To be considered a good financial performer, a company's profit must also be able to cover the company's equity and assets. However, PT AirAsia Indonesia's profit has not been able to cover the assets and capital because the industry standard profitability ratio has not been met. To increase PT AirAsia Indonesia Tbk's profitability, this condition indicates that PT AirAsia Indonesia must evaluate and improve its profit, asset, and equity management efficiency and effectiveness.